Managing workplace negativity - Topchik, Gary S. (AMACOM, 2001)
"In Managing Workplace Negativity, Topchik explains how to spot this insidious killer of workplace efficiency, as well as how to put negative individuals, teams, and organizations back on the road to recovery." "Topchik illustrates that the outcomes of negativity can be surprisingly tangible, such as increased customer complaints, increased error rates, declining work quality - and particularly damaging in today's tough labor market - increased employee turnover." "But Topchik does much more than point out the problem. He presents a series of practical, easy-to-implement steps for improving your organization's health, as well as inoculating yourself against the infectious pessimism of others." "Managing Workplace Negativity is a tool for constructing positive, productive, and more enjoyable work environments. Even better, it serves as a fresh, new source of optimism for restoring balance and harmony to our professional lives."--Jacket